Emotional Intelligence and Risk Leadership on the Effectiveness of ISO 31000 Implementation in Organisation - Ardilo, Aldi (RSF Conference Series: Business, Management and Social Sciences, 2021)
ISO 31000 indicates that risk management is a science in which competencies are embedded in the individuals. It also emphasises the importance of having proper leadership while demonstrating the commitment towards the risk management implementation. Humans are emotional creatures—we could sometimes be influenced by the force of feelings, rather than rational discussion. This paper describes the dynamics of emotional intelligence and risk leadership in implementing risk management. The research used a qualitative-descriptive design with the verification strategy of case study. It used a non-probability sampling to individuals in the top management position. The findings suggest that without a proper level of emotional intelligence, it is difficult for leaders to cultivate an effective risk culture. These findings may equip decision makers on the interrelationships between emotional intelligence, risk culture, and organisation’s risk management maturity.